Implementation of E-Service in Population Administration Services at The Population Service and Bone Regency Civil Registration - Ulfa, Maria; Aslinda, Andi; Guntur, Muhammad (Universitas Negeri Makassar, 2023)
In essence, public service is the provision of services to the community for the needs of the community both in quality and quantity in the life of the country or government system. Service is the essential main task of the apparatus, as servants of the state and society. This research aims to research how e-service is implemented in population administration services at the Bone Regency Population and Civil Registration Service and the factors inhibiting e-service services in population administration services at the Bone Regency Population and Civil Registration Service. This type of research is qualitative using a descriptive approach. Data collection techniques are carried out by means of observation, interviews and documentation. The data analysis technique used consists of data collection, data condensation, data presentation and drawing conclusions. The results of the research show that the implementation of e-service in the Bone Population Administration Service at the Population and Civil Registration Service of Bone Regency has been running in accordance with the provisions of Minister of Home Affairs Regulation Number 7 of 2019 but has not been completely running well, human resources and facilities are inadequate, socialization What is being done to the public is not on target and they do not understand the Adminduk's online services as seen from the sending of documents that are not appropriate. This research can be a reference for research on the Implementation of E-Service in Population Administration Services using qualitative methods.